PELAKSANAAN MANAJEMEN PEMELIHARAAN GARDU DISTRIBUSI - Nurmiati Pasra; Permata Putri Ruswandi (Sutet, 2016)
The quality of services at the State Electricity Company should be improved by minimizing the interruption of the electrical power supply in the power distribution system of 20 kV. Create a effective process of supplying electrical power, the equipment used must be maintained in order to last long, for example equipment in distribution substations. Thorough maintenance activities carried out when the system is off, it means there are planned outage times. Methods of maintenance, there are Time Based Maintenance (TBM) and Condition Based Maintenance (CBM). Both methods have been adopted. TBM until 2013 and CBM from 2014 until now. At the time the company implemented method of TBM, its SAIDI is 1.34936 hour/customers/ year and its SAIFI is 398.1322 times/customer/year. Meanwhile, when CBM is applied, its SAIDI is 0.33110 hour/customers/year and its SAIFI is 65.5828 times/customer/year. The cost of maintenance with CBM is Rp495.311.340,00, which is cheaper than the TBM with its cost up to Rp1.272.924.480,00. It can be seen that the effective method is the CBM, which only execute maintenance activities on distribution substations when needed, but produce a better reliability index numbers with a more economical cost.